2011
DOI: 10.1016/j.coph.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Different in vivo functions of the two catalytic domains of angiotensin-converting enzyme (ACE)

Abstract: Angiotensin converting enzyme (ACE) can cleave angiotensin I, bradykinin, neurotensin and many other peptide substrates in vitro. In part, this is due to the structure of ACE, a protein composed of two independent catalytic domains. Until very recently, little was known regarding the specific in vivo role of each ACE domain, and they were commonly regarded as equivalent. This is not true, as shown by mouse models with a genetic inactivation of either the ACE N-or Cdomains. In vivo, most angiotensin II is produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 45 publications
2
68
0
Order By: Relevance
“…While angiotensin 1-7 was suggested as a possible ACE N-domain specific substrate by in vitro analysis, examination of the N-KO and C-KO mice showed no difference in blood or kidney levels of this peptide under basal conditions (Ong et al, 2011). Thus, these data are more consistent with the findings of Rice than with those of Deddish.…”
Section: B Chloride Dependencysupporting
confidence: 69%
See 1 more Smart Citation
“…While angiotensin 1-7 was suggested as a possible ACE N-domain specific substrate by in vitro analysis, examination of the N-KO and C-KO mice showed no difference in blood or kidney levels of this peptide under basal conditions (Ong et al, 2011). Thus, these data are more consistent with the findings of Rice than with those of Deddish.…”
Section: B Chloride Dependencysupporting
confidence: 69%
“…A similar study after continuous administration of ACE inhibitors also demonstrated elevation of AcSDKP in humans . Studies in rats and mice are similar to the human studies (Junot et al, 1999;Bernstein et al, 2011). For example, the plasma AcSDKP concentration in N-KO mice was 7.3-fold that measured in wild-type mice.…”
Section: B Chloride Dependencysupporting
confidence: 61%
“…60 Since Ac-SDKP is a substrate exclusively of this domain of ACE, these mice have a seven-fold elevation of this peptide in the serum. 61 In contrast, serum angiotensin II concentrations are unaffected because the ACE C-terminal catalytic domain remains intact. 60,61 These mice have a normal hematocrit and normal peripheral leukocyte count and subtype percentages (ref.…”
Section: Ace and Hscmentioning
confidence: 99%
“…In part, this is because of the structure of ACE1, a protein composed of 2 independent catalytic domains denoted by the N and C domains. 4 Two isoforms of ACE1 have been found, which are expressed from alternative promoters in a single gene. 5 Somatic ACE is a glycoprotein with a molecular mass of 130 to 190 kDa that contains the 2 domains.…”
mentioning
confidence: 99%
“…The actions of Ang II have been implicated in many cardiovascular conditions, such as hypertension, atherosclerosis, coronary heart disease, restenosis, and heart failure. 2 ACE1, through catalysis of Ang-(1-7) to Ang- (1)(2)(3)(4)(5), inactivates the ACE2-Ang-(1-7)-Mas receptor axis, which acts as a buffer of RAS. The ACE1 inhibitors protect from end-organ damages by maintaining the ACE2-Ang-(1-7)-Mas axis.…”
mentioning
confidence: 99%